The diverse effects of transforming growth factor-β and SMAD signaling pathways during the CTL response - Chandiran, Karthik; Cauley, Linda S. (Frontiers in Immunology, 2023)
Cytotoxic T lymphocytes (CTLs) play an important role in defense against infections with intracellular pathogens and anti-tumor immunity. Efficient migration is required to locate and destroy infected cells in different regions of the body. CTLs accomplish this task by differentiating into specialized subsets of effector and memory CD8 T cells that traffic to different tissues. Transforming growth factor-beta (TGF-beta) belongs to a large family of growth factors that elicit diverse cellular responses via canonical and non-canonical signaling pathways. Canonical SMAD-dependent signaling pathways are required to coordinate changes in homing receptor expression as CTLs traffic between different tissues. In this review, we discuss the various ways that TGF-betaand SMAD-dependent signaling pathways shape the cellular immune response and transcriptional programming of newly activated CTLs. As protective immunity requires access to the circulation, emphasis is placed on cellular processes that are required for cell-migration through the vasculature.